The Spread of Democracy in China - Muhamad Ibnu Armandhani (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2024)
The spread of democratic ideas and economic growth in China—as suggested by the logic of modernization theory—have not initiated political reform toward democracy in China. Various literatures have attempted to explain this failure by emphasizing economic and social learning factors that clash with China’s national interests rather than emphasizing the context of its spreading process. Generally, this article aims to explain China’s failure to reform its politics toward democracy by focusing on the context of spreading democratic ideas in China. Specifically, this article aims to elucidate the relevance and continuity of the spread of democratic ideas in China during the May Fourth Movement of 1919, the Tiananmen Movement of 1989, and the Umbrella Movement of 2014, to the fifth wave of the Asian Barometer Survey (ABS). This article adopts a constructivist paradigm and constitutive localization theory to explain the failure of political reform in China. The findings suggest that Chinese local political ideas have influenced the spreading process of democratic ideas, contributing to China’s failure to acquire political reform toward democracy.